Prevalence of Diabetic Retinopathy and Its Associated Factors among Diabetic Patients at Debre Markos Referral Hospital, Northwest Ethiopia, 2019: Hospital-Based Cross-Sectional Study - Tilahun M; Gobena T; Dereje D; Welde M; Yideg G (Diabetes, Metabolic Syndrome and Obesity, 2020)
Melkamu Tilahun,1 Teshome Gobena,2 Diriba Dereje,2 Mengistu Welde,2 Getachew Yideg3 1Department of Biomedical Sciences (Medical Physiology), College of Medicine and Health Sciences, Debre Markos University, Debre Markos, Ethiopia; 2Department of Biomedical Sciences, College of Medicine and Health Sciences, Jimma University, Jimma, Ethiopia; 3Department of Biomedical Sciences (Medical Physiology), College of Medicine and Health Sciences, Debre Tabur University, Debre Tabur, EthiopiaCorrespondence: Melkamu TilahunDepartment of Biomedical Sciences (Medical Physiology), College of Medicine and Health Sciences, Debre Markos University, PO Box 269, Debre Markos, EthiopiaTel +251 93-355-5884Fax + 0587780673Email melkamutilahunalamir@gmail.comBackground: Diabetic retinopathy is a well-known sight-threatening microvascular complication of diabetes mellitus. Currently, 93 million people live with diabetic retinopathy worldwide. There are insufficient studies addressing the prevalence of diabetic retinopathy and risk factors in Ethiopia.Objective: To assess the prevalence of diabetic retinopathy and its associated factors among diabetic patients on follow-up at Debre Markos Referral Hospital, northwest Ethiopia, 2019.Methods: This institution- based cross-sectional study was conducted among 302 patients. They were selected through systematic sampling. Explanatory data were extracted from medical records and interviews. Blood pressure, weight, height, and visual acuity tests were assessed. Retinal examination was performed with a Topcon TRC-NW7SF fundus camera. Data were entered in EpiData 3.1 and exported in to SPSS 20 for analyses. Binary logistic regression with 95% CIs was used for analyses. Simple binary logistic regression followed by multiple binary logistic regression analysis was conducted to identify associated factors.Results: There were 302 patients in this study, of which 57 (18.9%) had diabetic retinopathy. Among the diabetic retinopathy patients, 75.4% had the preproliferative type. Four in ten (37.7%) of the patients had visual acuity problems. Poor glycemic control (AOR 4.58, 95% CI 1.86– 11.31), > 10 years’ diabetes duration (AOR 3.91, 95% CI 1.86– 8.23), body-mass index > 25 kg/m2 (AOR 3.74, 95% CI 1.83– 7.66), and hypertension (AOR 3.39, 95% CI 1.64– 7.02) were factors significantly associated with diabetic retinopathy.Conclusion: About a-fifth of diabetic patients had diabetic retinopathy. Diabetic retinopathy was significantly associated with glycemic control, hypertension, body-mass index, and duration of illness. Routine assessment and early control of those associated factors may be important in reducing both the prevalence and impact of diabetic retinopathy, as evidenced in the current study.Keywords: diabetes mellitus, diabetic retinopathy, associated factor, Ethiopia